STRATEGI PENGEMBANGAN OBJEK WISATA ALAM PUNCAK BILA KABUPATEN SIDRAP - Jannah, Miftahul; Madani, Muhlis; Haerana, Haerana (Universitas Muhammadiyah Makassar, 2024)
This study aims to determine the strategy of the Department of Youth, Sports and Tourism in Developing the Puncak Bila Nature Tourism Object in Sidrap Regency. The type of research used in this study is a qualitative descriptive research method using a phenomenological approach. Data collection is done through observation, interviews and documentation. The results of the study show that the development of natural tourism objects peaks when the important role of human resources is required to carry out development activities. The budget issued reached Rp. 500,000,000 of the total budget of Rp. 700,000,000 of the total will be prepared by 2023. The rides currently provided are swimming pools, Flying Fox, Motor ATVs, it's just that you need to pay attention to water quality and maintain the cleanliness of the facilities as well as the need for additional rides and photo spots.